Assessment of Indonesian Life Insurance Customer Behavior: Investment Return Potential For Evaluating Market Discipline - Titiek Irewati (Eduvest - Journal of Universal Studies, 2024)
Market discipline, which concerns aspects of monitoring and the ability of market participants to play a role in influencing management behavior, is an aspect of the financial industry that has not yet clearly existed in the life insurance industry in Indonesia.  This condition is the background of a study that aims to determine the possibility of market discipline in the life insurance industry in Indonesia through observation of the relationship between the acquisition of investment returns of life insurance companies with the acquisition of new business and termination of contracts or lapse policies.  Testing based on sample data from 27 life insurance companies (Financial Statements published by OJK) resulted that: can accept the hypothesis of a positive correlation (unidirectional) trend between investment returns and new businesses, but cannot accept the hypothesis that there is a negative tendency (not in the same direction) between investment returns and policy lapse.  The market (life insurance consumers) has not been able to express disapproval of the company's performance that is not in accordance with the wishes.